تحدي الأمن الغذائي في الجزائر: دراسة قياسية خلال الفترة 1995 -2015 - بن عيسى، كمال الدين Ibn Issa, Kamalulddin; كبيري، فتيحة (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2018)
Since independence, although the Algerian sector of agriculture has witnessed several changes, the local food production remains insufficient to satisfy the local demand especially that of a wide consumption. Therefore, a need for importation is considered as a way to satisfy food deficit. From the other hand, the Algerian economy is based on revenues coming from fuel export in order to match the food gap. This situation is regarded as a risk to its food security at both its long and medium terms, mainly due to the significant decline of fuel prices for a long period of time. Additionally, the use of biofuel technology as an alternative strategy recalls for alarm clock to find out solution for this situation under investigation.
Keywords: الأمن الغذائي -- المؤسسات الزراعية -- الفجوة الغذائية -- الإنتاج الزراعى -- الجزائر